Effect of cycling cadence on contractile and neural properties of knee extensors - Lepers, R.; Millet, G. Y.; Maffiuletti, N. A. (Medicine & Science in Sports & Exercise, 2001)
Purpose: This study investigated the effect of prior prolonged cycling exercise performed at different cadences on subsequent neuromuscular characteristics. Methods: Eight well-trained triathletes sustained 80% of their maximal aerobic power during 30 min at three cadences: the freely chosen cadence (FCC), FCC-20%, and FCC+20%. Maximal isometric and concentric (120 degrees.s-1 and 240 degrees.s-1) torques were recorded before and after the exercise. Central activation, neural (M-wave), and contractile (isometric muscular twitch) parameters of quadriceps muscle were also analyzed by electrical stimulation of the femoral nerve. Results: Reductions in maximal isometric (P < 0.01) and concentric torques at 120 degrees.s-1 (P < 0.05) were found after exercise. Central activation levels fell significantly (P < 0.05) by 13-16% depending on the pedaling rate. Although the M-wave did not significantly change after exercise, the ratio EMG RMS/M-wave amplitude decreased significantly (P < 0.01) on both vastus lateralis and vastus medialis muscles for FCC-20% and FCC but not for FCC+20%. Significant decreases in maximal twitch tension (P < 0.01), maximal rate of twitch development (P < 0.01), and time to half relaxation (P < 0.01) were observed postexercise with no effect of cadence. Conclusions: These findings suggest that force reduction after prolonged cycling is attributable to both central and peripheral factors but is not influenced by the pedaling rate in a range of FCC +/- 20%.